Effectiveness of Regional Regulation No. 13/2019 on Handling the Poor in North Lampung - Rohmiyati, Rohmiyati; Dwiono, Sugeng (Journal of Law Science, 2025)
This study aims to analyze the effectiveness of the implementation of Regional Regulation of North Lampung Regency Number 13 of 2019 concerning the Handling of the Poor and Abandoned Children. The method employed is a normative legal approach with descriptive analysis of secondary data, which includes primary, secondary, and tertiary legal materials. The results indicate that the implementation of this regulation faces various challenges, including a lack of accurate data regarding the conditions of the poor, budget constraints due to the economic impact of the COVID-19 pandemic, and the absence of shelters for abandoned children. Furthermore, the limited media coverage of these programs hinders public awareness and community participation. Proposed recommendations include the development of a comprehensive database, securing adequate funding, establishing shelters for abandoned children, and implementing effective media strategies. By addressing these challenges, it is hoped that the Regional Regulation can be more effective in improving the welfare of the poor and abandoned children in North Lampung Regency